Cardiovascular and abdominal flow alterations in adults with morphologic evidence of liver disease post Fontan palliation. (15th October 2020) - Abbasi Bavil, Elyar; Yang, Hyun Kyung; Doyle, Matthew G.; Kim, Tae Kyoung; Karur, Gauri; Bhagra, Catriona; Bhagra, Sai; Oechslin, Erwin N.; Ross, Heather; Roche, S. Lucy; Gonzalez, Rafael Alonso; Amon, Cristina H.; et al.
Abstract: Background: Although morphologic abnormalities in the liver are commonly encountered post Fontan palliation, the relationships between hepatic morphology, vascular flows, and clinical status remain incompletely understood. We therefore aimed to explore flow characteristics in hepatic and intestinal vessels and to examine cardiovascular associations with liver disease. Methods: This was a retrospective study of adults post Fontan palliation undergoing clinically indicated cardiovascular magnetic resonance imaging (MRI). Patients were included if MRI flow quantification was available for cardiac, hepatic and intestinal vessels; patients were excluded if phase-contrast flow imaging was insufficient for analysis. Results: Thirty patients were studied (median age at MRI 28.5 years [range 19–47]). Eighteen subjects (60%) were classified as having morphologic liver disease according to validated criteria based on available MRI imaging. Abdominal and cardiovascular flows were quantified. Patients with morphologic liver disease had a 41% reduction in superior mesenteric artery (211 ± 124 versus 358 ± 181 mL/min/m 2, p = .004), a 36% reduction in hepatic vein (496 ± 247 versus 778 ± 220 mL/min/m 2, p = .01), a 31% reduction in portal vein (399 ± 133 versus 580 ± 159 mL/min/m 2, p = .004), and an 18% reduction in Fontan pathway flows (1358 ± 429 versus 1651 ± 270 mL/min/m 2, p = .04) compared with the remaining population. Adverse cardiovascular events were not associated with morphologic liver disease. Conclusion: Morphologic liver disease appears to be associated with flow alterations within the heart, liver and intestine post Fontan palliation. These novel observations suggest that a potential relationship exists between morphologic disease and vascular flows thereby providing further insights into the pathophysiology of liver disease in this high-risk population. Highlights: Magnetic resonance imaging (MRI) can quantify abdominal flows using phase contrast (PC) imaging. Fontan patients with morphologic liver disease have decreased hepatic and intestinal flows on PC MRI. Adverse cardiovascular events were not increased in Fontan patients with liver disease on MRI.